2012
DOI: 10.1007/s11605-011-1720-6
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Environment in Ileal Pouch Mucosa: α5 Defensin Up-regulation as Predictor of Chronic/Relapsing Pouchitis

Abstract: Defensins are small cationic peptides with antibacterial activity expressed in Paneth cells (α-defensins) or generally in intestinal epithelial cells (β-defensins) that have a profound effect on gut microbiota. Chronic pouchitis, which occurs in 5% of patients after restorative proctocolectomy and can cause pouch failure, is associated to a significant increase of Clostridiaceae spp. The aim of this study was to gain further insight in the pathogenesis of pouch dysbiosis by exploring defensin expression. Thirt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 52 publications
(75 reference statements)
1
7
0
3
Order By: Relevance
“…Amyloid fibril generation is also important for AMP activities, mediating disruption of microbial cell membranes (Sood et al, 2008), neutralization of bacterial endotoxins (Wang et al, 2014), and pathogen agglutination and entrapment (Chu et al, 2012; Torrent et al, 2012). However, dysregulated AMP oligomerization can also lead to serious pathologies, including inflammation, tissue degeneration (Paulsen et al, 2002; Pereira et al, 1996; Reinholz et al, 2012; Scarpa et al, 2012), and deposition as amyloid in at least three human amyloidopathies (Araki-Sasaki et al, 2005; Ciornei et al, 2006; Kee et al, 2008; Linke et al, 2005; Millucci et al, 2011; Pálffy et al, 2009; Reinholz et al, 2012; Scarpa et al, 2012; Yamaguchi et al, 2007; Zhao et al, 2008). Thus, AMP oligomerization carries a potential for protective/damaging duality in human health.…”
Section: Introductionmentioning
confidence: 99%
“…Amyloid fibril generation is also important for AMP activities, mediating disruption of microbial cell membranes (Sood et al, 2008), neutralization of bacterial endotoxins (Wang et al, 2014), and pathogen agglutination and entrapment (Chu et al, 2012; Torrent et al, 2012). However, dysregulated AMP oligomerization can also lead to serious pathologies, including inflammation, tissue degeneration (Paulsen et al, 2002; Pereira et al, 1996; Reinholz et al, 2012; Scarpa et al, 2012), and deposition as amyloid in at least three human amyloidopathies (Araki-Sasaki et al, 2005; Ciornei et al, 2006; Kee et al, 2008; Linke et al, 2005; Millucci et al, 2011; Pálffy et al, 2009; Reinholz et al, 2012; Scarpa et al, 2012; Yamaguchi et al, 2007; Zhao et al, 2008). Thus, AMP oligomerization carries a potential for protective/damaging duality in human health.…”
Section: Introductionmentioning
confidence: 99%
“…When the intestinal ecosystem is in balance, epithelial cells produce defensins such as α-defensins 5 and 6, and β-defensin 1, as a strong chemomechanical barrier to control the intestinal microbiota and maintain immunological homeostasis. Upregulation of α-defensin 5 is a predictor of chronic/relapsing pouchitis, and can mediate shifts in the composition of the microbiota that favor inflammation (Scarpa et al, 2012 ). During inflammation or infection, additional defensins such as β-defensin 2 and 3 are induced as a type of “demand system” (Semple and Dorin, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial, antiviral, and immunomodulatory activities of HD5 are host protective during infection [27,48,49,53,54]. Considering the relationship between the upregulated serum HD5 with clinical-pathological parameters and long-term renal outcome, as well as the expression of HD5 in the damage proximal tubules in IgAN patients, the present study indicated that HD5 as a regulator of intestinal immunology may be a reliable marker of the progression of IgAN and associate with the renal function of IgAN.…”
Section: Discussionmentioning
confidence: 63%
“…HD5 exhibits high antimicrobial activity against Enterobacteriaceae. Overexpression of HD5 resulted in increased Clostridiaceae by decreasing competing bacteria families, leading to chronic/relapsing pouchitis [48]. Expression balance of HD5 is essential for the intestinal homeostasis [49].…”
Section: Disease Markersmentioning
confidence: 99%